Asuhan Kebidanan Komprehensif Pada Ny. S Umur 43 Tahun Dengan Preeklamsia dan Faktor Resiko Tinggi di BPM Ny. R Wilayah Kerja Puskesmas Bumiayu Kabupaten Brebes Tahun 2023 - Dewi Maulina Azmi; Hafsah Hafsah; Riyanti Riyanti (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
According to WHO (2022) the MMR in the world is 91.46/100,000 live births, the MMR in ASEAN (2022) is 235/100,000 live births (ASEAN secretariat, 2022). In Indonesia, the MMR in 2022 is 230/100,000 live births (Indonesian Ministry of Health, 2022). The MMR in Central Java in 2022 was 98.6/100,000 live births (Central Java Health Office, 2022) and the MMR at the Bumiayu health center in 2022 was 2 cases (Bumiayu Health Center, 2020-2022). Objective : To reduce morbidity and mortality rates of mothers and infants in Brebes district, especially the working area of Puskesmas Bumiayu. this research is a qualitative descriptive study, the type of research used in this study is using a comprehensive case study approach. Comprehensive case study research is a method for understanding individuals that is carried out interactively (Notoadmojo, 2019). Research Results : This comprehensive care found a gap in theory and practice in pregnancy and childbirth care. Conclusion: Comprehensive Midwifery Care for Mrs. S aged 43 years with preeclampsia and high risk factors at BPM Mrs. R in the working area of the bumiayu health center from third trimester pregnancy, childbirth, newborns, postpartum and family planning with the Varney and soap midwifery approach.